Clinical and biochemical investigation of male patients exhibiting membranous cytoplasmic bodies in biopsied kidney tissues; a pitfall in diagnosis of Fabry disease - Hitoshi Sakuraba; Takahiro Tsukimura; Toshie Tanaka; Tadayasu Togawa; Naoki Takahashi; Daisuke Mikami; Sachiko Wakai; Yasuhiro Akai (Society of Diabetic Nephropathy Prevention, 2015)
Background: The existence of membranous cytoplasmic bodies in biopsied kidney tissues is one of the important findings when considering Fabry disease as the first choice diagnosis. However, there are possible acquired lysosomal diseases associated with pharmacological toxicity, although less attention has been paid to them. Case Presentation: We experienced 3 male patients presenting with proteinuria and specific pathological changes strongly suggesting Fabry disease. We sought detailed clinical and biochemical information to avoid a wrong diagnosis. The patients were examined clinically and pathologically, and plasma α-galactosidase A (GLA) activity and the globotriaosylsphingosine (lyso-Gb3) concentrations were measured. Electron microscopic examination revealed numerous membranous inclusion bodies in podocytes, and biochemical analysis revealed normal GLA activity and a normal lyso-Gb3 level in plasma, showing that they did not have Fabry disease. They suffered from hyperlipidemia, myeloma, or lupus nephritis. They had received pitavastatin calcium, clarithromycin, loxoprofen and/or prednisolone, and there was no medication history of cationic amphiphilic drugs. Conclusions: In this case series, the etiology of the inclusions was not clarified. However, these cases indicate that careful attention should be paid on diagnosis of patients exhibiting inclusion bodies in kidney cells, and it is important to confirm their past and present illnesses, and medication history as well as to measure the GLA activity and lyso-Gb3 level.